Synthetic cDNA Construction of Granulocyte Stimulating Factor - Yahia Falih Mohammed; Aysar Ihsan Falih (American Journal of Biology and Natural Sciences, 2025)
INTRODUCTION: Granulocytes are a category of white blood cells characterized by the presence of granules in their cytoplasm. They are also called polymorphonuclear leukocytes (PMN or PML) because of the varying shapes of the nucleus, which is usually lobed into three segments. In common parlance, the term polymorphonuclear leukocyte often refers specifically to neutrophil granulocytes, the most abundant of the granulocytes. Granulocytes or PMN are released from the bone marrow by the regulatory complement proteins. There are three types of granulocytes, distinguished by their appearance under Wright's stain: Neutrophil granulocytes, Eosinophil granulocytes and Basophil granulocytes Objectives: Cloning of GCSF cDNA and expression of the granulocyte colony stimulating factor protein. Methodology Primer designing: Oligonucleotides were manually designed and synthesized, in even numbers, corresponding to the double stranded DNA, in a sequential manner. The G-CSF nucleotide sequence (Accession number NM_000759) of 522 bp, was divided in 12 short sequences of approximately 50 bp each. Oligonucleotides contained overlapping regions of about 10 bases at their 5'- and 3'-ends. The primers employed in the present study are given in Table 1. The primers P1 and P12 contained the restriction sites for, respectively, Nde I and Bam HI. The 522 bp final PCR product was agarose-gel purified and cloned into the pJET1.2 Blunt vector (Fermantas). CONCLUSION: Full length cDNA was constructed and cloned into blunt end vector. Further the cloned product need to express to get the recombinant H-GCSF protein to purify it. Construction and cloning of h-GCSF cDNA was completed and the protein purification has to be standardized.